Przesilenia kanclerskie w Cesarstwie Niemieckim w 1917 r. na łamach krakowskiego Głosu Narodu - Markowska, Anna (Saeculum Christianum. Pismo Historyczne, 2019)
The article concerns governmental crises and changes in the chancellor’s position that took place in the German Empire in the period between July and November 1917. It was possible to cover this issue thanks to the analysis of articles published in the Krakow daily newspaper “Głos Narodu”. This paper referred to direct correspondents from Berlin, German press agencies, or information from the German press. The author wants to show a few months of tensions in German internal politics and present various behind-the-scenes games of political parties in the government. The situation in the Empire was important for us, Poles, because the year 1917 and the reports from the fronts of World War I gave rise to more and more hopes for regaining independence.